The Representativeness of Participants With Severe Mental Illness in a Psychosocial Clinical Trial - Lally, John; Watkins, Rochelle; Nash, Sarah; Shetty, Hitesh; Gardner-Sood, Poonam; Smith, Shubulade; Murray, Robin M.; Gaughran, Fiona (Frontiers in Psychiatry, 2018)
Introduction Cardiovascular morbidity and mortality are increased in severe mental illnesses (SMI). Trials of psychosocial health interventions to improve physical health in SMI, including in treatment-resistant schizophrenia, have shown some benefit. However, the representativeness of participants in such trials has not been determined. Method We utilised an anonymised case register to determine if participants in a randomised controlled trial (RCT) of a novel psychosocial health intervention aiming to improve physical health in SMI had similar severity of illness to eligible non-participants. A retrospective database analysis was performed, using Health of the Nation Outcome Scale (HoNOS) data from the sample of patients participating in the IMPaCT (Improving Physical health and reducing substance use in Psychosis) RCT (n=293) compared to all eligible participants with a psychotic illness (n=774). Results The mean total HoNOS score in the eligible comparator population (Mean = 9.09, SD = 5.8, range=0-30) was significantly greater than that of the IMPaCT RCT participants (Mean = 7.16, SD = 4.7, range =0-26), (t = 3.810, p=0.006), as was the degree of overall illness severity and functional impairment, as measured by HoNOS. Conclusion This study shows for the first time that the patient population participating in an RCT of a lifestyle intervention for those with SMI had a better mental health status at entry to the trial, than the total eligible population, although there was no difference in physical health needs. This has relevance to the applicability of RCTs of lifestyle interventions in service planning and suggests that when people are more unwell, greater effort may be needed to include them in psychosocial interventions. A more careful and focused recruitment approach should be followed to improve the participation of the more severely ill patients in psychosocial interventions in order to enhance the external validity of such studies.